2021
DOI: 10.3389/fimmu.2021.625346
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Aryl Hydrocarbon Receptor Signaling Pathway in Breast Cancer Development

Abstract: Activation of the aryl hydrocarbon receptor (AhR) through environmental exposure to known human carcinogens including dioxins can lead to the promotion of breast cancer. While the repressor protein of the AhR (AhRR) blocks the canonical AhR pathway, the function of AhRR in the development of breast cancer is not well-known. In the current study we examined the impact of suppressing AhR activity using its dedicated repressor protein AhRR. AhRR is a putative tumor suppressor and is silenced in several cancer typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…MCF-7 and MCF-7-AHR-KO cells were cultured in DMEM high glucose (4.5 g/l) medium (PAN Biotech) supplemented with 10% FBS and antibiotics/antimycotics. The generation and characterization of HaCaT-shAHR and HaCaT-EV cells ( Fritsche et al, 2007 ) and MCF-7-AHR-KO cells ( Vogel et al, 2021 ) has been previously described. HepG2 cells were cultured in RPMI 1640 containing 10% FBS and antibiotics/antimycotics (PAN Biotech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCF-7 and MCF-7-AHR-KO cells were cultured in DMEM high glucose (4.5 g/l) medium (PAN Biotech) supplemented with 10% FBS and antibiotics/antimycotics. The generation and characterization of HaCaT-shAHR and HaCaT-EV cells ( Fritsche et al, 2007 ) and MCF-7-AHR-KO cells ( Vogel et al, 2021 ) has been previously described. HepG2 cells were cultured in RPMI 1640 containing 10% FBS and antibiotics/antimycotics (PAN Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…The generation of CYP1A1-KO and NRF2-KO HaCaT keratinocytes was carried out as described previously ( Vogel et al, 2021 ). The respective gRNAs ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A complementary study [ 152 ] showed that the AhR blunted the effects of doxorubicin on cell viability in MDA-MB-231 cells and this was due in part to AhR regulation of aldo-ketoreductase 1C3. The AhRR decreases availability of functional AhR by competing for ARNT, and using transgenic mice overexpressing AhRR, it was shown that AhRR suppresses mammary tumor development and AhR-dependent growth and the inflammatory gene COX2 (±TCDD) [ 153 ]. Similar results were observed in MCF-7 and MDA-MB-231 cells treated with etoposide and doxorubicin; both drugs induced the percentage of apoptotic cells which was further enhanced after cotransfection with an AhRR expression plasmid.…”
Section: Ahr and Ahr Ligands Enhance Mammary Carcinogenesismentioning
confidence: 99%
“…AhR promotes E3 ubiquitin ligase activity on selective protein substrates; ligand-activated AhR engages steroid hormone receptors for ubiquitination and proteasomal degradation [24][25][26][27] . Given that carbidopa decreases the levels of ERα in MCF7 cells and the supporting evidence for the involvement of AhR in carbidopa-mediated ubiquitination and proteasomal degradation of ERα in the process, we sought direct evidence for AhR activation by carbidopa.…”
Section: Carbidopa Activates Ahr Promotes Its Localization To the Nuc...mentioning
confidence: 99%
“…It is upregulated in some cancers (e.g., colorectal cancer, pancreatic cancer, renal cancer, esophageal cancer) but down-regulated in others (e.g., breast cancer, prostate cancer) [22]. Activation of AhR as a therapeutic approach has been demonstrated by several studies with AhR agonists such as raloxifene [23][24][25]. Similar to raloxifene, carbidopa is also an FDA-approved drug and therefore can be potentially repositioned for cancer therapy if its anticancer e cacy is demonstrated convincingly.…”
Section: Introductionmentioning
confidence: 99%